THE ECONOMIC BURDEN OF ALL-TERRAIN VEHICLE-RELATED ADULT DEATHS IN THE US WORKPLACE, 2003–2006. (7th October 2012) - Helmkamp, J; Elyce, B; Marsh, S; Aitken, M; Campbell, C
Abstract : Background: All-terrain vehicles are used in a variety of industries and occupations. Objective: To estimate the societal economic burden associated with occupation-related ATV fatalities among civilian persons more than 17 years of age in the USA from 2003–2006. Methods: ATV death data were obtained from the Bureau of Labor Statistics' annual Census of Fatal Occupational Injuries. Costs were estimated using a model employing a cost-of-illness method developed by the National Institute for Occupational Safety and Health. Results: From 2003–2006, 129 occupation-related ATV deaths occurred among persons >17 years of age in the USA, nearly doubling from 20 deaths in 2003–39 deaths in 2006. The collective lifetime cost of the deaths was $103.6 million (M) with a 4-year mean of $803 100 and a 4-year median of $772 100. Decedents aged 35–54 years accounted for one-third of the deaths (n=41) at a cost of $50.1 M. Montana had the most deaths (13). Fifty-two per cent of the deaths were overturns costing $48.3 M. Eighty-four (65%) of the deaths were workers in agricultural production at a cost of $62.3 M. Significance: Short-term investment in prevention measures, such as training and helmets for workers, could provide lasting dividends by preventing occupation-related ATV deaths and reducing their economic impact.